Integration of photo-supercapacitor utilizing polypyrrole/reduced graphene oxide intermediate bifunctional electrode - Lau, Siaw Cheng (2017)
With the continued industrialization and development of the world economy, the need for a clean source of renewable energy is becoming ever more urgent. Furthermore, despite the recent rise in global oil production due to fracking, on a time horizon of one or two hundred years, oil reserves will ultimately dwindle, along with supply. Sunlight is an abundant energy source that is more than capable of providing for the world’s energy needs. In order to generate and simultaneously store the photo-generated energy for substantial use even during the night, a supercapacitor is coupled with solar cell, which turned into an integrated photo-supercapacitor. In this work, a photo-supercapacitor with three electrodes configuration was fabricated by the integration of titania (TiO2)-based dye-densitized solar cell (DSSC) with a symmetrical supercapacitor utilizing polypyrrole/reduced graphene oxide (PPy/rGO) as an electrode active material. The photoanode of DSSC was composed of compact and mesoporous TiO2 layer. Compact TiO2 layer was formed via aerosol-assisted chemical vapor deposition (AACVD) method while the mesoporous TiO2 layer was deposited using doctor’s blade method. The PPy/rGO materials were formed through electrochemical deposition. Double-sided-electrodeposited PPy/rGO material served as an intermediate electrode which was bifunctional; acting as a counter electrode for the DSSC to permit electrolyte regeneration, and charge storage for the supercapacitor. Before the integration, the isolated DSSC and supercapacitor were characterized, and the power conversion efficiency (PCE) of DSSC was 2.4 %, while the specific capacitance of the supercapacitor was 308.1 F/g. The performance of the integrated photosupercapacitor was tested under a light illumination of 100 mW/cm2. The photosupercapacitor experienced a small voltage drop of 0.024 V with high charge/discharge durability and long lifetime. Remarkably, the photo-supercapacitor possessed a specific capacitance of 124.7 F/g and a retention percentage of 70.9 % was obtained after 50 consecutive cycles of charge/discharge. This cheap graphene-based and light-weight integrated device showed a promising performance in both effectiveness and stability, thus it opened the door for future selfpowered electrochemical energy storage system. To further improve this device, development on the intermediate electrode and device packaging should be taken into consideration.